Ex post appraisal: What lessons can be learnt from EU cohesion funded transport projects?. (January 2015) - Kelly, Charlotte; Laird, James; Costantini, Stefano; Richards, Phil; Carbajo, José; Nellthorp, John
Abstract: This paper is concerned with project level outcomes of 10 large transport projects spread over eight countries that had benefited from EU Cohesion and ISPA funding. These are analysed within a cost benefit analysis framework with comparisons being made between the ex ante and ex post cost benefit analyses. The research finds that despite much attention being placed on the issue of optimism bias over the last decade it still remains prevalent. It also finds that there is a clear need to improve the quality and consistency of ex ante analysis particularly in the areas of capital cost estimation, travel demand modelling and risk analysis. Additionally our research identifies the limited role that formal decision making tools such as cost benefit analysis and multi-criteria analysis play in the decision making process of the countries surveyed. The benefit of undertaking ex post cost benefit analysis is maximised when a set of schemes are analysed – thereby allowing patterns in outcomes and weaknesses in ex ante methodologies to be identified. Ex post work is not without its challenges particularly in defining the counterfactual and addressing institutional memory loss. Highlights: Findings from an ex post study of ten large transport schemes in eight countries. Optimism bias remains prevalent. Ex ante cost benefit analyses typically could be improved in the areas of capital cost estimation, travel demand modelling and risk analysis. The role of cost benefit analysis in decision-making remains limited. Ex post evaluation programmes are illuminating in the way they identify patterns of strength and weakness in the methodologies being applied ex ante .